Pervasive cloud computing technologies : future outlooks and interdisciplinary perspectives - Grandinetti, Lucio, 1941-; Pisacane, Ornella; Sheikhalishahi, Mehdi; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, PA 17033, USA) : IGI Global, 2014)
"This book explores the latest innovations with cloud computing and the impact of these new models and technologies, presenting case studies and research on the future of cloud computing technologies and its ability to increase connectivity of various entities of the world"--Provided by publisher.
A general purpose and hyperspecialization model of future computing -- The enabling technologies for cloud computing -- Service delivery models and deployment options -- Standardization -- Cloud security -- Cloud computing and big data -- Economics of cloud computing -- Cloud in enterprises and manufacturing -- Cloud in science -- Cloud computing and operations research -- Cloud computing and healthcare -- Green computing: a dual technology for HPC and cloud computing.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF title page (viewed on 01/22/2014).
Keywords: Cloud computing -- Case studies; Big data management; Cloud in industry, science, public administration and government; E-science; Economics and business facet of cloud computing; Forensics; Green computing; Healthcare; Management science; Standardization and security in the cloud; Electronic books